2007
DOI: 10.1124/dmd.107.017459
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Human Isoforms of Drug Transporters Contribute to the Hepatic and Renal Transport of Olmesartan, a Selective Antagonist of the Angiotensin II AT1-Receptor

Abstract: ABSTRACT:Olmesartan, a novel angiotensin II AT1-receptor antagonist, is excreted into both bile and urine, with minimal metabolism. Because olmesartan is a hydrophilic anionic compound, some transporters could be involved in its hepatic and renal clearance. In this study, we characterized the role of human drug transporters in the pharmacokinetics of olmesartan and determined the contribution of each transporter to the overall clearance of olmesartan. Olmesartan was significantly taken up into human embryonic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
71
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 122 publications
(73 citation statements)
references
References 26 publications
1
71
1
Order By: Relevance
“…The mechanism by which urinary excretion of olmesartan was reduced after the co-administration of pravastatin is unclear and still needs to be clarified. Recent in vitro studies indicated that organic anion transporter 3 (OAT3) expressed at the basolateral membrane of renal proximal tubule epithelial cells is predominantly involved in renal uptake of both pravastatin and olmesartan (Hasegawa et al 2002;Yamada et al 2007). The drug-drug interaction via OAT3 between pravastatin and olmesartan may account for the reduction of olmesartan renal excretion in the co-administration phase; however, the interaction via MRP2, which also is expressed in the kidney, cannot be ruled out (Kivistö et al 2005;Nakagomi-Hagihara et al 2006).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The mechanism by which urinary excretion of olmesartan was reduced after the co-administration of pravastatin is unclear and still needs to be clarified. Recent in vitro studies indicated that organic anion transporter 3 (OAT3) expressed at the basolateral membrane of renal proximal tubule epithelial cells is predominantly involved in renal uptake of both pravastatin and olmesartan (Hasegawa et al 2002;Yamada et al 2007). The drug-drug interaction via OAT3 between pravastatin and olmesartan may account for the reduction of olmesartan renal excretion in the co-administration phase; however, the interaction via MRP2, which also is expressed in the kidney, cannot be ruled out (Kivistö et al 2005;Nakagomi-Hagihara et al 2006).…”
Section: Resultsmentioning
confidence: 99%
“…Recent in vitro studies using OATP1B1-expressing Xenopus laevis oocytes (Nakagomi-Hagihara et al 2006) and HEK293 cells (Yamada et al 2007) have indicated that olmesartan is a substrate of OATP1B1. Olmesartan is eliminated from the body through hepatic and renal routes without extensive metabolism (Laeis et al 2001).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…3 Therefore, the effect of genetic variations of single transporters on the pharmacokinetics of olmesartan is considered to be small.…”
Section: Discussionmentioning
confidence: 99%
“…1 Some studies have suggested that organic anion-transporting polypeptide 1B1 (gene name, SLCO1B1) and organic anion-transporting polypeptide 1B3 (SLCO1B3) are involved in hepatic uptake and that the ATP-binding cassette, sub-family C member 2 (multidrug resistance-associated protein (MRP) 2, ABCC2), is involved in the biliary excretion of olmesartan. 2,3 Membrane transporters have important roles in the uptake, distribution and excretion of endogenous compounds and xenobiotics. Polymorphisms in genes encoding transporters have been investigated extensively and appear to be associated with altered transporter activity.…”
Section: Introductionmentioning
confidence: 99%